PENDAMPINGAN PEMASARAN DIGITAL UMKM MELALUI PRODUKSI KONTEN VISUAL DI PKK KELURAHAN BAUSASRAN - Nurcholis, Muhammad Tofa; Saputro, Uyock Anggoro; Fauzi, Moch Farid; Chaniago, Annisa Silvia; Guric, Bonaventura Isaac (Jurnal Abdi Insani, 2025)
This community service activity was conducted in Bausasran Village, focusing on assisting MSME members of the PKK in producing video content and editing using the CapCut application. The background of this program is the limited ability of MSMEs to create engaging visual content, even though video plays an essential role in improving product promotion and attractiveness on social media. The aim of this activity is to enhance partners’ skills in digital marketing management through mastering video shooting and editing techniques with CapCut. The method was carried out through a one-day intensive training consisting of hands-on product video creation, introduction to CapCut’s main features, and personalized mentoring for participants. The evaluation was conducted using pre- and post-training questionnaires to measure the improvement in participants’ knowledge and skills. The results show a significant improvement from 24 participants. The average pre-training score was 20.7, which increased to 38.7 in the post-training session, with an average improvement of 18 points or 159.3%. A total of 22 participants showed improvement, 2 participants remained the same, and none experienced a decrease. These findings indicate that the training effectively enhanced participants’ skills in managing video content for product promotion. The participants not only gained an understanding of the importance of digital marketing but also developed the ability to produce simple promotional videos ready for publication on social media. This mentoring activity proved effective in supporting the digital transformation of micro, small, and medium enterprises (MSMEs) at the village level, while also strengthening their product marketing strategies through visual content.